'The church should know its place': The passions and the interests of urban struggle in post-atheist Russia. Issue 5 (20th October 2021) - Kormina, Jeanne
ABSTRACT: Urban space is a familiar place of religious-secular struggles in postsocialist world today, foremost due to the deprivatization of religion followed by attempts of religious organizations and new non-secular publics to find an acceptable public space in the post-secular world. At the same time, secular publics tend to be highly sensitive to interventions of religious 'Others' into the public sphere. In some cases, these struggles between secular and non-secular publics resemble 'right to the city' movements, when secularist activists claim the city as a space where presence of religion should be limited, separated and controlled by secular onlookers. The essay introduces the notion of 'passionate secularism' in order to stress the centrality of the passions, understood as sincere movements of the heart, in the rhetoric of the secularists which help them to articulate their high cultural status and moral superiority. It analyses a controversial 2016 proposal by authorities in St. Petersburg, Russia to transfer ownership of St. Isaac's Cathedral, a powerful symbol of local identity and a sort of an urban sacred place, from state to church and the protests unfolded in Winter and Spring 2017. They essay focuses on the ways how participants in the urban struggle historicized the lines and borders which were seen to divide inhabitants of the city as political or cultural descendants of the creators of the Soviet state, and discusses various historical loops they experience – as traps, burden or heritage.